Di'ao Xinxuekang: Therapeutic Potential in Cardiovascular Diseases - Zhang, Shengyu; Li, Lingli; Deng, Mingying; Wang, Yanan; Shen, AiZong; Zhang, Lei (Current Molecular Pharmacology, 2021)
Background: Cardiovascular disease is the leading cause of death in both developed and developing countries. Di'ao Xinxuekang (DAXXK) is a pure Chinese medicine herbal preparation refined from dioscin extracted from the roots of Dioscorea panthaica Prain et Burk and Diosorea nipponica Makino. Objective: To evaluate the application of DAXXK in Cardiovascular disease. Methods: We searched and summarized all the studies on DAXXK and Cardiovascular disease in Pubmed, Google, and CNKI. Results: Modern pharmacological studies have shown that DAXXK has pharmacological effects such as dilating blood vessels, lowering blood pressure and cardiac load, improving hemodynamics, lowering blood lipids and anti-platelet aggregation, and is widely used for the therapy of various kinds of cardiovascular diseases, including hypertension, atherosclerosis, coronary heart disease (CHD), angina pectoris (AP) and myocardial infarction. We provide an overview of the clinical efficacy, molecular mechanisms, safety and therapeutic potential of DAXXK in the treatment of cardiovascular disease, aiming to provide clues and evidence for clinical decision-making. Conclusion: DAXXK exerts cardiovascular protection by regulating a variety of cardiovascular disease- related signaling pathways.
Keywords: coronary artery disease